Menggali Potensi Lokal Dengan Pengembangan UMKM Dan Peluang Desa Wisata Melalui KKN Tematik Di Desa Carangwulung, Wonosalam, Jombang - Aprilianti, Dennis; Huda, Syamsul; Utami, Anisa Fitria (Universitas Gajah Putih, Indonesia, 2023)
Carangwulung Village in the Wonosalam sub-district is developing its potential with the concept of a tourist village. This village offers a variety riches tourism potential. The problems experienced by Carangwulung residents are the lack of ability to develop local tourism potential and the lack of marketing of processed carangwulung products. In community serviceWhich carried out by students through the UPN